2018
DOI: 10.3892/or.2018.6788
|View full text |Cite
|
Sign up to set email alerts
|

High expression of TMEM40 contributes to progressive features of tongue squamous cell carcinoma

Abstract: Transmembrane protein 40 (TMEM40) is a 23-kDa protein and its association with tongue squamous cell carcinoma (TSCC) remains unclear. This study aimed to investigate the expression and clinical significance of TMEM40 in TSCC and its roles in TSCC cells. Immunohistochemical analysis was performed to detect the expression levels of TMEM40 in 60 tongue tissue samples. Furthermore, TMEM40 was overexpressed and inhibited in two TSCC cell lines by transfection with pEZ-M98-TMEM40 plasmid or TMEM40 small interfering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Out of the 180 high-probability p63 target genes 32 (28 up- and four down-regulated) are also identified as being commonly up- or down-regulated in SCCs compared to non-SCC cancers ( Cancer Genome Atlas Research Network et al, 2018 ; Table 1 ). Importantly, several of the genes commonly up-regulated by p63 as well as in SCC have been identified to promote SCC growth or invasion, such as LAD1 ( Abe et al, 2019 ), TMEM40 ( Zhang et al, 2019 ), FGFBP1 ( Czubayko et al, 1997 ), IL1B ( Lee et al, 2015 ), FAT2 ( Dang et al, 2016 ), FOSL1 ( Usui et al, 2012 ), LPAR3 ( Brusevold et al, 2014 ), MMP14 ( Pang et al, 2016 ), and RASSF6 ( Zheng et al, 2019a ). Therefore, we asked whether the set of 28 up-regulated direct p63 targets correlates with patient survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 180 high-probability p63 target genes 32 (28 up- and four down-regulated) are also identified as being commonly up- or down-regulated in SCCs compared to non-SCC cancers ( Cancer Genome Atlas Research Network et al, 2018 ; Table 1 ). Importantly, several of the genes commonly up-regulated by p63 as well as in SCC have been identified to promote SCC growth or invasion, such as LAD1 ( Abe et al, 2019 ), TMEM40 ( Zhang et al, 2019 ), FGFBP1 ( Czubayko et al, 1997 ), IL1B ( Lee et al, 2015 ), FAT2 ( Dang et al, 2016 ), FOSL1 ( Usui et al, 2012 ), LPAR3 ( Brusevold et al, 2014 ), MMP14 ( Pang et al, 2016 ), and RASSF6 ( Zheng et al, 2019a ). Therefore, we asked whether the set of 28 up-regulated direct p63 targets correlates with patient survival.…”
Section: Resultsmentioning
confidence: 99%
“…296such as LAD1(Abe et al, 2019), TMEM40(Zhang et al, 2019), FGFBP1(Czubayko et al, 297 1997), IL1B(Lee et al, 2015), FAT2(Dang et al, 2016), FOSL1(Usui et al, 2012), LPAR3…”
mentioning
confidence: 99%
“…A shift in expression from a full-length Tnnt1 protein (in TSCs) to a shorter isoform in TGCs may have a similar role in migration and actin dynamics in TGCs [ 80 , 81 ]. Other genes with differentially expressed exons are known to be involved in several biological processes including cell growth, invasion, migration, apoptosis, and differentiation [ 82 , 83 ]. Cell type-specific expression of the identified exons may be important in maintaining stemness or inducing differentiation of trophoblast stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…TMEM40 encodes a 23 kDamulti-pass membrane protein. A previous study revealed that TMEM40 is localized at chromosome 3p25.2 and is believed to play a key role in collagen-induced arthritis ( 20 ). The expression levels of TMEM40 were significantly higher in bladder cancer tissues and were associated with clinical grade ( 21 ).…”
Section: Discussionmentioning
confidence: 99%